P-chiral 1-phosphanorbornenes: from asymmetric phospha-Diels–Alder reactions towards ligand design and functionalisation12. Issue 5 (17th August 2015) - Möller, Tobias; Wonneberger, Peter; Sárosi, Menyhárt B.; Coburger, Peter; Hey-Hawkins, Evamarie
Abstract : A building set for chiral phosphorus. The principle of stereotopic face differentiation is successfully applied to a PC bond. A divergent ligand synthesis is feasible after reduction of the chiral auxiliary. Abstract : The principle of stereotopic face differentiation was successfully applied to 2 H -phospholes which undergo a very efficient and highly stereoselective Diels–Alder reaction giving phosphorus-chiral 1-phosphanorbornenes with up to 87% yield. The observed reaction pathway has been supported by theoretical calculations showing that the cycloaddition reaction between 2 H -phosphole3a and the dienophile (5 R )-(−)-menthyloxy-2(5 H )-furanone (8 ) is of normal electron demand. Optically pure phosphanes were obtained by separation of the single diastereomers and subsequent desulfurisation of the sulfur-protected phosphorus atom. Finally, divergent ligand synthesis is feasible by reduction of the chiral auxiliary, subsequent stereospecific intramolecular Michael addition, and various functionalisations of the obtained key compound13a . Furthermore, the unique structural properties of phospanorbornenes are presented and compared to those of phosphanorbornanes.